THERMAL PERFORMANCE EVALUATION OF ROOM AIR CONDITIONERS EVAPORATORS - Piske, A. C.; Moura, L. M.; Mendes, N. (Revista de Engenharia Térmica, 2005)
This work presents a thermal performance evaluation of a fin-and-tube evaporator - that is widely used in packaged air conditioning equipment - using a balanced calorimeter developed to simulate similar running conditions. The calorimeter determines the heat rate absorbed by the evaporator, providing qualitative analysis of performance for a given geometry. The calorimeter inside air is dried out due to the condensation process on the evaporator under test during the transient period. By this way it is possible to preview the humidity of the calorimeter domain and its influence with the instrumentation measurement. The heat transfer rate absorbed by the evaporator is obtained by a lumped approach using the energy conservation that is applied to the calorimeter domain, and is taken on the boundaries of the equipment. Physical parameters such as overall heat transfer coefficient for several types of fins can then be predicted in order to provide information for improving the energy-efficiency-oriented design. The uncertainties are estimated by the propagation of relative effects. Uncertainties are evaluated taking into account the systematic effects. Results are shown in terms of evaporator overall heat transfer coefficient and heat transfer rate as a function of inlet air temperature.